2008
DOI: 10.1002/pssc.200779177
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of minority carrier lifetime for InAlAs/InGaAs high electron mobility transistors by using 1.55‐μm femto‐second pulse laser

Abstract: The minority carrier lifetime (τ) of High electron mobility transistors (HEMTs) made using the InAlAs/InGaAs material system lattice‐matched to the InP substrate had been obtained from optical response measurements with a 1.55‐μm femto‐second pulse laser where the laser was illuminated onto the backside of a wafer. The drain current of HEMTs associated with the optical pulse was detected using a digitizing oscilloscope, and τ was estimated from the exponential dependence of drain current on time. In our curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…We have been studying the physical properties of a phenomenon expressed in high electron mobility transistors (HEMTs) of the kind used in ultra-highspeed field effect transistors (FETs) [3][4][5]. Our previous research on inhibitors of carrier transport led us to propose fusing a high-speed device with a photo-responsive device [6].…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying the physical properties of a phenomenon expressed in high electron mobility transistors (HEMTs) of the kind used in ultra-highspeed field effect transistors (FETs) [3][4][5]. Our previous research on inhibitors of carrier transport led us to propose fusing a high-speed device with a photo-responsive device [6].…”
Section: Introductionmentioning
confidence: 99%
“…A current-gain cut-off frequency (f t ) of 628 GHz [2] and a maximum oscillation frequency (f max ) of 1.2 THz have been reported [1]. In our previous study regarding the effect of optical irradiation on InAlAs/InGaAs HEMT characteristics, we demonstrated that a shift of threshold voltage (V TH ) in InAlAs/InGaAs HEMTs is caused by the change in the Fermi level due to the holes accumulated in the source region [3,4]. The carrier lifetime of accumulated holes is dominated by Auger recombination of holes in the two-dimensional electron gas (2DEG) [3][4][5].…”
mentioning
confidence: 95%
“…Furthermore, we have shown that InAlAs/InGaAs HEMTs have a high responsivity when they are used as optical receivers [5]. Recently, we have demonstrated that InAs-PHEMTs can operate as not only high-speed transistors but as ultra-high speed optical receivers [3][4][5][6].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The carrier lifetime of accumulated holes is dominated by the recombination of holes with two-dimensional electron gas (2DEG) [5,6]. Furthermore, we showed that InAlAs/ InGaAs HEMTs have a high responsivity when they are used as optical receivers [7].…”
mentioning
confidence: 98%